2018
DOI: 10.3390/su10041018
|View full text |Cite
|
Sign up to set email alerts
|

Turning Farmers into Business Partners through Value Co-Creation Projects. Insights from the Coffee Supply Chain

Abstract: This study examines the empowerment of low-power, vulnerable stakeholders of global, complex supply chains as one effective strategy to increase value co-creation and to moderate the vulnerabilities that threaten supply chain resilience. Previous scholars have indicated the necessity of investigating the concept of value co-creation further by including various stakeholder perspectives and suggesting systems of evaluation. This research thus focuses on low-power smallholder farmers within the coffee supply cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 55 publications
1
32
0
2
Order By: Relevance
“…To provide one example to clarify such a design of a multi-stakeholder value map, we can look at what happens in the coffee industry. In previous studies on such a global and complex supply chain, scholars tried to revolutionize the traditional stakeholder theory perspective (i.e., the firm) and adopted that of farmers, who were considered vulnerable and powerless stakeholders in the coffee value chain (Civera et al, 2019;Candelo et al, 2018). This change of perspective allowed scholars to more effectively individuate the issues arising from farmers' relationships with other stakeholders, including the firm (i.e., global coffee roaster) and to better identify the areas in which farmers needed empowerment to become active partners in the joint value creation process.…”
Section: The Multi-stakeholder Value Mapmentioning
confidence: 99%
“…To provide one example to clarify such a design of a multi-stakeholder value map, we can look at what happens in the coffee industry. In previous studies on such a global and complex supply chain, scholars tried to revolutionize the traditional stakeholder theory perspective (i.e., the firm) and adopted that of farmers, who were considered vulnerable and powerless stakeholders in the coffee value chain (Civera et al, 2019;Candelo et al, 2018). This change of perspective allowed scholars to more effectively individuate the issues arising from farmers' relationships with other stakeholders, including the firm (i.e., global coffee roaster) and to better identify the areas in which farmers needed empowerment to become active partners in the joint value creation process.…”
Section: The Multi-stakeholder Value Mapmentioning
confidence: 99%
“…Indeed, agriculture can be considered as “a legacy from local people traditions and activities” (Rogerso, ); it reinforces the process of cultural identity and promotes local territories and communities (Donert & Light, ; Jansen‐Verbeke, ). Furthermore, this can create new opportunities to protect and maintain core elements of a certain territory where some social and economic conditions exist (Candelo, Casalegno, Civera, & Mosca, ; Civera, De Colle, & Casalegno, ), which, together with climate change, represent a challenge and a threat (Sun et al, ). Again, it becomes clear that it is possible to link the benefit of rural tourism to stakeholder theory, which captures the efforts of creating common benefits (Byrd, ).…”
Section: Food People's Perceptions and Rural Tourismmentioning
confidence: 99%
“…From the present coffee farmers’ point of view, local communities in developing countries are helped by NGOs and coffee roasters to augment their social inclusion and sense of entrepreneurship—at least in the farming sector (Civera et al, ). Thus, some communities have reached a fairly strong level of awareness of how to improve income in new ways, even though, for some coffee farmers’ communities, the migration of youth from productive country areas still represents a threat (Candelo et al, ). Despite this, Torres () and, years later, Lacher and Nepal () indicated that the service sector could be linked with agriculture with some benefits, which have an impact on the destination's image (Tapachai & Waryszak, ) and on the local community's social wellness and inclusion (Joliffe, ).…”
Section: Rural Tourism In Equatorial Countries: Facing Threats With Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue concerning the inclusion of local ties gains a strong value when a certain territory also depends on tourism. Indeed, tourism represents a good means of livelihood for local (indigenous) communities, especially when they are powerless and marginalised, since it may eventually lead to economic change and major social inclusion (Potts, 2003;Phillip et al, 2010;Jamali & Neville, 2011;Candelo et al, 2018;Civera et al, 2019).…”
Section: Theoretical Foundation Of the Importance Of (Real) Local Stamentioning
confidence: 99%